Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/bit.25938
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer rates in shaken culture vessels from Fernbach flasks to microtiter plates

Abstract: By a sulfite oxidation method, oxygen transfer rates (OTRs) were determined in 11 types of culture vessels from 2.8-L Fernbach (FB) flasks to 96-, 48-, and 24-well square deepwell microtiter plates (MTPs). OTRs ranged from 140 mM/h in 250-mL Ultrayield™ flasks shaken at 300 rpm with a 50 mm diameter shaker throw to 5 mM/h in unbaffled FBs shaken at 200 rpm with a 25 mm throw. Baffles in FBs increased OTRs 6-12-fold under various shaking conditions, and up to five-fold in 250-mL flasks, depending on the type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The sodium sulfite oxidation method was used to determine k L a values as previously described . The method is based on the reaction of sodium sulfite, a reducing agent, with dissolved oxygen in the presence of a catalyst, usually a divalent cation such as Cu 2+ or Co 2+ , to produce sulfate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sodium sulfite oxidation method was used to determine k L a values as previously described . The method is based on the reaction of sodium sulfite, a reducing agent, with dissolved oxygen in the presence of a catalyst, usually a divalent cation such as Cu 2+ or Co 2+ , to produce sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…The sodium sulfite oxidation method was used to determine k L a values as previously described. [28][29][30] The method is based on the reaction of sodium sulfite, a reducing agent, with dissolved oxygen in the presence of a catalyst, usually a divalent cation such as Cu 21 or Co 21 , to produce sulfate. The concentration of sodium sulfite (Na 2 SO 3 , Tianjin Dingshengxin Chemical Industry, Tianjin, China) in each tube was kept higher than 0.04 M to guarantee that the oxygen concentration in the liquid was zero.…”
Section: Experimental Methods Of Determining K L Amentioning
confidence: 99%
“…Galactaric acid production by T. reesei has previously been demonstrated in flask cultures [8], but at much lower concentrations than can be obtained in bioreactors [7]. Running and Bansal [12] demonstrated that 24-well plates can have as good or better oxygen transfer as shaken flasks, depending on the shaking regime applied, and 24-well plates are increasingly being used for the cultivation of filamentous fungi [1315]. It is therefore useful to assess whether galactaric acid production by T. reesei could be scaled down for production in 24-well plates using pectin as substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the venting holes of 1.5 mm in diameter the oxygen consumption of the microbial culture was not limited by the lid. Running and Bansal performed OTR studies with 24‐, 48‐, and 96‐well MTP using customized lids with venting holes of 4.5 mm in diameter. They found that the OTR was not limited by the size of the holes.…”
Section: Discussionmentioning
confidence: 99%